Spatiotemporal Dynamic of Ostreococcus lucimarinus in IMTA System at Enclosed Sea (Hangzhou Bay) East China Sea Using Environmental DNA (eDNA) - Dyah Muji Rahayu; Peimin He; Kejun Li; Jinlin Liu; Sarwo Edy Wibowo; Ester Restiana Endang Gelis; Bs Monica Arfiana (Sriwijaya Journal of Environment, 2023)
Integrated Multi-Trophic Aquaculture (IMTA) is growing fast in China, in order for cultivation with this system to continue. Through eDNA approach in able to detect Ostreococcus lucimarinus which include picoeukaryotic in IMTA system at enclosed sea (Hangzhou Bay). Information about this species and their ecological placement in the IMTA system is still very limited. eDNA is an ecological approach that can detect supply down to the species level in monitoring aquatic ecology in the IMTA system. The purpose of this study was to determine the taxonomy and guarantees of Ostreococcus lucimarinus and the role of this species in the IMTA system descriptively. Through high throughput sequencing, the taxonomic results of Ostreococcus lucimarinus and confinement of this picoekaryotic species were highest in winter with a total of 599,632 ind. Based on the sampling location, the highest abundance were in aquaculture areas of 337,165 ind. The approach using eDNA has proven to be capable of detecting up to the species level as well as spatiotemporal abundance dynamics of Ostreococcus lucimarinus.